The Effect of High Doses of Dextromethorphan on The Human Nervous System - Marwa Jewi; Shaban, Fatimah Nameer (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Dextromethorphan (DXM) is a commonly used nonprescription cough suppressant that has gained field of science attention with its growing complex pharmacological effects and increased incidences of nonmedical use. This review is focused on pharmacokinetic, pharmacodynamics and CNS effects of DXM, especially on its action mechanism and the interaction with neural circuits and neurotransmitter systems. Although DXM has retained clinical utility as an antitussive, and has demonstrated potential as an off-label agent for neuropsychiatric disease, the recreational use of high doses can have harmful effects on the nervous system. At high doses DXM is capable of dissociation and hallucination similar to those induced by some opioids and NMDA antagonists, altering both mental status and cognition while being associated with neurotoxic effects. In this article, review and compare the similarities and differences between DXM and classic opioids in terms of their potential for abuse and their neurological effects. By case examples and existing epidemiological data, it also highlights the mounting abuse of DXM, most notably by children and young adults, posing a pressing public health challenge. Legislation on DXM is also described and differences in legislative response worldwide are highlighted. Finally, the article finishes by emphasizing the requirement for further studies involving other disciplines to detail the long-term neurological consequences of DXM abuse and to promote integrated public health interventions targeting education, prevention, and clinical treatment.